2020
DOI: 10.1063/1.5140561
|View full text |Cite
|
Sign up to set email alerts
|

High temperature electrical transport properties of MBE-grown Mg-doped GaN and AlGaN materials

Abstract: This paper discusses the results of high temperature resistivity and Hall effect studies of Mg-doped GaN and Al x Ga 1-x N epilayers (0.05 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…In this way, an impurity band of the finite width is formed and holes can hop between different impurity atoms. A similar observation of hopping conductivity at relatively high temperature was published in the case of heavily Mg-doped epitaxial layers [8,26,27]. In region C, this mechanism dominated the conduction process.…”
Section: Results Of Electron Transport Characterizationsupporting
confidence: 79%
See 1 more Smart Citation
“…In this way, an impurity band of the finite width is formed and holes can hop between different impurity atoms. A similar observation of hopping conductivity at relatively high temperature was published in the case of heavily Mg-doped epitaxial layers [8,26,27]. In region C, this mechanism dominated the conduction process.…”
Section: Results Of Electron Transport Characterizationsupporting
confidence: 79%
“…Theoretical pv at RT is also given. For benchmarking purpose literature data for GaN:Mg are provided[26,27,34] in the last column (NA-NDeffective density of acceptors, EMgionization energy of Mg acceptor).…”
mentioning
confidence: 99%
“…It was pointed out that annealing in an ambient nitrogen environment between 870 and 1120 K for one hour led to no change in the electrical properties of the material grown by reactive MBE with ammonia. [ 6 ] However in our previous work, [ 7 ] from the electrical transport measurements carried out in the temperature range from 300 K up to 1000 K, we showed that for temperatures T exceeding some critical value T C ≥ 800 K, the resistivity ρ and Hall concentration p H became time‐dependent. After the annealing process, a more than ≈60% irreversible decrease of the sample resistivity as well as an increase of the free hole concentration has occurred.…”
Section: Introductionmentioning
confidence: 72%
“…The crystal growth procedure was the same as the one applied to the samples in the previous study. [ 7 ] The materials under study were grown on 2 inch c‐plane (0001) sapphire substrates by MBE in a “Riber 32 P” reactor. Effusion cells were used for Ga and Al elements, the Mg dopant was supplied by a RIBER VCOR110 valved cell and ammonia (NH 3 ) was used as the nitrogen source.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, significant efforts have been devoted to growing highly conductive p-type AlGaN epilayers with high Al contents by MBE. [79][80][81]131,132] Although the polarization and superlattice (SL) doping methods have also been studied intensively and devices using these approaches have also been demonstrated, [23,[133][134][135][136] in what follows we shall focus on the state-of-the-art p-type conduction from p-type AlGaN epilayers by Mg doping.…”
Section: Highly Conductive P-type Algan Epilayersmentioning
confidence: 99%